Romania : Technical Assistance Report on Improving Revenues from the Recurrent Property Tax. (IMF Staff Country Reports; Country Report ;, 2022)
The current area-based property tax system in Romania is inefficient, producing revenue below its potential, while the taxable value determination is inequitable and complex. Indeed, the property tax only generated 0.6 percent of GDP in 2021 vs. the average of 1.8 percent of GDP in the OECD economies, or 0.9 percent of GDP in EU-27. Meanwhile, significant scope for improving both buoyancy and efficiency of the property tax system exists, not least through the elimination of multiple exemptions, addressing the current inadequate and fragmented self-declaration system of residential buildings that translates into incomplete fiscal cadasters.